2023
DOI: 10.1001/jamanetworkopen.2022.50954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Faculty Parental Leave Policies at Medical Schools Ranked by US News & World Report in 2020

Abstract: ImportancePhysician parents, particularly women, are more likely to experience burnout, poor family-career balance, adverse maternal and fetal outcomes, and stigmatization compared with nonparent colleagues. Because many physicians delay child-rearing due to the rigorous demands of medical training, favorable parental leave policies for faculty physicians are crucial to prevent physician workforce attrition.ObjectiveTo evaluate paid and unpaid parental leave policies at medical schools ranked by US News &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…More than one-quarter of respondents reported taking an extended leave of 12 weeks or greater, notably higher than the 14.9% of US medical schools currently offering faculty 12 weeks or more of fully paid maternity leave. 32 In support of single-center data, 14 nearly half of women with children in our study reported passing up opportunities for career advancement and reducing work hours to accommodate parenthood. Results from a 2019 prospective study 15 of early-career physicians suggested that these accommodations may be more prevalent among women vs men physicians and may begin soon after completion of training; within 6 years of training, 22.6% of women physicians worked part time vs 3.6% of men physicians, and 77.5% of those working part time cited family as the most influential factor in this decision.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…More than one-quarter of respondents reported taking an extended leave of 12 weeks or greater, notably higher than the 14.9% of US medical schools currently offering faculty 12 weeks or more of fully paid maternity leave. 32 In support of single-center data, 14 nearly half of women with children in our study reported passing up opportunities for career advancement and reducing work hours to accommodate parenthood. Results from a 2019 prospective study 15 of early-career physicians suggested that these accommodations may be more prevalent among women vs men physicians and may begin soon after completion of training; within 6 years of training, 22.6% of women physicians worked part time vs 3.6% of men physicians, and 77.5% of those working part time cited family as the most influential factor in this decision.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, our results highlight the degree to which women in medicine altered their careers to accommodate pregnancy and parenthood. More than one-quarter of respondents reported taking an extended leave of 12 weeks or greater, notably higher than the 14.9% of US medical schools currently offering faculty 12 weeks or more of fully paid maternity leave . In support of single-center data, nearly half of women with children in our study reported passing up opportunities for career advancement and reducing work hours to accommodate parenthood.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Slostad and colleagues provide an in-depth 2020 update of parental leave policies for physicians at medical schools ranked by US News & World Report . This study provides useful data regarding the scarcity of institutions who follow the American Academy of Pediatrics’ recommendations for 12 weeks of paid parental leave.…”
mentioning
confidence: 99%
“…Through this lens, efforts should include family benefits for those who may become parents through less traditional routes and should promote the well-being of physicians without children. Slostad et al provide valuable insight into the paucity of support for adoption and foster care, routes to parenthood often pursued by same-sex couples and the 1 in 4 female physicians experiencing infertility . Policies that perpetuate gender- and sexual orientation–based inequalities must be amended.…”
mentioning
confidence: 99%